Програмный сопособ распознавания объекта на плоскости при помощи внешней системы технического зрения - Гориславец, Д. Ю. (ХНУРЕ, 2019)
Technical vision systems is special sensoric device, which can help take high quality images, their following processing and transformation. This system today are very relevant and in demand in different areas of human activity, because they can be used for recognition of object types and their location, for example, on mass conveyor production, in security systems, etc. This technical vision system can be used to process live video streaming